The Impact Of Turnover On Employee Performance At The Regional Drinking Water Company (Pdam) In Mamuju Regency - Ainaya Ifditiya Ramadhani; Irma; Agus Halim (CV. SINAR HOWUHOWU, 2026)
The purpose of this study is to examine how employee turnover rates impact employee performance at the Mamuju Regency Water Company (PDAM). In a public service organization like PDAM, the sustainability of clean water services is highly dependent on the stability and performance of the human resources who manage it. High employee turnover rates can cause various problems, such as increased workloads, disrupted coordination, and decreased service quality to the public. This study used a quantitative approach with a survey method of 60 PDAM Mamuju Regency employees selected using a purposive sampling technique. Data were collected through a questionnaire with a five-point Likert scale that measured employee performance and turnover rates. Data were analyzed using simple linear regression and descriptive statistics. The results showed that turnover had a negative and significant impact on employee performance. This means that the higher the turnover rate, the lower the performance level of PDAM Mamuju Regency employees. These results indicate that to reduce turnover rates and maintain the quality of employee performance in providing services to the public, effective human resource management is crucial.